Antimicrobial Activity of Some of the Locally Available Vegetables - Kusuma, M.P.; Chandana Lakshmi, M.V.V. (Asian Journal of Chemistry, 2010)
In the present work, in vitro antimicrobial properties of different vegetables which are used in day to day life is studied. The vegetable extracts were tested against pathogenic bacteria E. coli, Staphylococcus aureus, Salmonella typhimurium, Pseudomonas aeruginosa, Clostridium tetanii and Streptococcus bacilli following spread plate method. The aqueous extracts of the different parts of vegetables are having antimicrobial properties. In the present investigation it was found that the epicarp of Ash gourd has greater inhibitory activity among the tested extracts on all the test strains.